Modeling of interactive cooperation's instrument "Virtual board" for project "Kherson Virtual University 2.0" - Ye.О.Kozlovskiy (Kherson State University, 2008)
In the article preconditions are considered for creation in the distance learning system studies the effective model of tutor and students co-operation. And also the description and principles of planning of similar models.